Intensity-dependent gene expression after aerobic exercise in endurance-trained skeletal muscle - Daniil V Popov; Pavel A Makhnovskii; Nadia S Kurochkina; Evgeny A Lysenko; Tatiana F Vepkhvadze; Olga L Vinogradova (Termedia Publishing House, 2018)
We investigated acute exercise-induced gene expression in skeletal muscle adapted to aerobic training. Vastus lateralis muscle samples were taken in ten endurance-trained males prior to, and just after, 4 h, and 8 h after acute cycling sessions with different intensities, 70% and 50% · VO2max. High-throughput RNA sequencing was applied in samples from two subjects to evaluate differentially expressed genes after intensive exercise (70% · VO2max), and then the changes in expression for selected genes were validated by quantitative PCR (qPCR). To define exercise-induced genes, we compared gene expression after acute exercise with different intensities, 70% and 50% · VO2max, by qPCR. The transcriptome is dynamically changed during the first hours of recovery after intensive exercise (70% · VO2max). A computational approach revealed that the changes might be related to up- and down-regulation of the activity of transcription activators and repressors, respectively. The exercise increased expression of many genes encoding protein kinases, while genes encoding transcriptional regulators were both up- and down-regulated. Evaluation of the gene expression after exercise with different intensities revealed that some genes changed expression in an intensity-dependent manner, but others did not: the majority of genes encoding protein kinases, oxidative phosphorylation and activator protein (AP)-1-related genes significantly correlated with markers of exercise stress (power, blood lactate during exercise and postexercise blood cortisol), while transcriptional repressors and circadian-related genes did not. Some of the changes in gene expression after exercise seemingly may be modulated by circadian rhythm.